Kemampuan Aparat Pemerintah Desa dan Efektivitas Pengelolaan Keuangan Desa - Yunianingrum Yunianingrum; Lala M Kolopaking (Departemen Sains Komunikasi dan Pengembangan Masyarakat, Fakultas Ekologi Manusia, IPB, 2018)
The capability of rural government officials has an important role in the effectiveness of village financial management. This research’s objectives are to analyze the capability of rural government officials, to analyze the effectiveness of village financial management and to analyze the relationship between rural government officials' capability to the effectiveness of village financial management in two villages, Bringinwareng village and Guyangan village. The results show that there is a diversity of capabilities of rural government officials. Bringinwareng village (good financial management) has a good officials capability compared to Guyangan village (poor financial management) that has the capability of officials at a moderate level. The level of effectiveness of the financial management of Bringinwareng village is better because transparency, accountability, participation, and ratios of village financial effectiveness tend to be high. In contrast to Guyangan village which has moderate effectiveness due to low transparency, moderate accountability and participation, but has a high ratio of village financial effectiveness. Based on the results of research that has been tested statistically shows that there is a correlation between the capability of rural government officials with the effectiveness of village financial management, both in Bringinwareng village and Guyangan village.Keywords: rural government officials, capability, village financial management ABSTRAKKemampuan aparat pemerintah desa memiliki perananan penting dalam keefektifan pengelolaan keuangan desa. Penelitian ini bertujuan untuk menganalisis kemampuan aparat pemerintah desa, menganalisis keefektifan pengelolaan keuangan desa dan menganalisis hubungan kemampuan aparat pemerintah desa terhadap efektivitas pengelolaan keuangan desa di dua desa, yaitu Desa Bringinwareng dan Desa Guyangan. Hasil penelitian menunjukkan ada keragaman kemampuan aparat pemerintah desa. Desa Bringinwareng (pengelolaan keuangan baik) memiliki kemampuan aparat yang baik dibandingkan Desa Guyangan (pengelolaan keuangan kurang baik) yang memiliki kemampuan aparat pada tingkat sedang. Tingkat efektivitas pengelolaan keuangan Desa Bringinwareng lebih baik, karena transparansi, akuntabilitas, partisipatif, dan rasio efektivitas keuangan desa cenderung tinggi. Berbeda dengan Desa Guyangan yang memiliki efektivitas sedang karena transparansi yang rendah, akuntabilitas dan partisipatif yang sedang, tetapi memiliki rasio efektivitas keuangan desa yang tinggi. Berdasarkan hasil penelitian yang telah diuji secara statistik menunjukkan bahwa terdapat hubungan antara kemampuan aparat pemerintah dengan efektivitas pengelolaan keuangan desa, baik di Desa Bringinwareng maupun di Desa Guyangan.Kata kunci: aparat pemerintah desa, kemampuan, pengelolaan keuangan desa